2022
DOI: 10.4103/ijo.ijo_1635_21
|View full text |Cite
|
Sign up to set email alerts
|

Localized surgical debridement for the management of orbital mucormycosis

Abstract: Purpose: To describe the role of localized debridement and instillation of amphotericin B for the management of orbital mucormycosis post COVID-19 infection with a view to avoid exenteration. Methods: The records of all patients with orbital mucormycosis post COVID-19 infection in the last 6 months from December 2020 to June 2021 were evaluated, and ten patients were identified who were successfully managed with localized debridement, that is, removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Murthy et al . [ 63 ] in a series of ten cases with ROCM showed that superior outcomes with localized surgical orbital debridement and application of amphotericin B gel to the site of debridement can help in salvaging the vision and avoiding exenteration in most cases. However, AMB has the potential to incite inflammation and could result in transient orbital soft-tissue edema when locally injected.…”
Section: Treatmentmentioning
confidence: 99%
“…Murthy et al . [ 63 ] in a series of ten cases with ROCM showed that superior outcomes with localized surgical orbital debridement and application of amphotericin B gel to the site of debridement can help in salvaging the vision and avoiding exenteration in most cases. However, AMB has the potential to incite inflammation and could result in transient orbital soft-tissue edema when locally injected.…”
Section: Treatmentmentioning
confidence: 99%
“…The orbital involvement was considered stage 3; in the early Stage 3, local debridements were considered the preferred surgical intervention, and exenteration is been suggested for advanced stage 3 disease with extensive orbital involvement. Previously explored globe-sparing treatment options for these patients are local surgical debridement[ 10 ] and TRAMB. [ 4 11 12 ] Additionally, we explored the peri-bulbar route to deliver site-centered amphotericin, and for selecting suitable patients, we categorized them based on their clinical and radiological extent of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies including patients with invasive fungal infections in general, and not mucormycosis specifically, and studies including mucormycosis cases not associated with COVID-19 and not separately with CAM cases were excluded. Sixteen studies were excluded due to unavailable–insufficient information [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Four studies were excluded as they included patients with non-microbiologically confirmed SARS-CoV-2 infection [ 25 , 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%